2019
DOI: 10.1002/cap.10078
|View full text |Cite
|
Sign up to set email alerts
|

Creeping Clinical Attachment After Acellular Dermal Matrix Augmentation to Attain Root Coverage

Abstract: Introduction This case report documents root coverage after using an acellular dermal matrix (ADM) combined with a tunneling procedure. The photographs and objective clinical measurements are presented to document a gain of new clinical attachment and subsequent creeping attachment. Case Presentation A 50‐year‐old male who demonstrated around 6 mm of recessions on the direct facial of teeth #6 through #11 had a root coverage procedure using an ADM. After 24 months, >90% of the recession defects at all sites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…At present, data on the amount of creeping attachment after the application of ADM are limited. Recently, Changi et al 44 reported that creeping attachment started 6 months after surgery and achieved 0.5‐2.5 mm over the 24‐month observation period. The amount was similar to those reported previously.…”
Section: Classified Discussion Of “Creeping Attachment”mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, data on the amount of creeping attachment after the application of ADM are limited. Recently, Changi et al 44 reported that creeping attachment started 6 months after surgery and achieved 0.5‐2.5 mm over the 24‐month observation period. The amount was similar to those reported previously.…”
Section: Classified Discussion Of “Creeping Attachment”mentioning
confidence: 99%
“…73 At present, data on the amount of creeping attachment after the application of ADM are limited. Recently, Changi et al 44…”
Section: Admmentioning
confidence: 99%
“…It is applied in periorbital soft tissue, dura mater, extraoral and intraoral, and oropharyngeal defects. It also has applications in skeletal support, nasal soft tissue, and tympanic membrane repair (1,(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Head and Neckmentioning
confidence: 99%
“…[2][3][4] This condition delivers dentin hypersensitivity, complicates the cleaning process, and interferes with esthetics. 5,6 Various treatment modalities can cover the root surface. Still, in patients with thin gingiva, it is necessary to choose the proper technique to reduce the risk of treatment failure.…”
Section: Introductionmentioning
confidence: 99%